The University of Auckland Sociology “Class of 1984” - Crothers, Charles (New Zealand Sociology, 2023)
A small but socially cohesive cohort of students graduated in 1984 after completing their master’s theses at the Department of Sociology, University of Auckland. As well as providing a case study of a postgraduate cohort and especially its cohesiveness, the symposium highlights the subsequent careers of the four key sociologists in the group, who have each made major contributions to Aotearoa New Zealand and world sociology through vigorous book and journal article publishing based on their research programmes. Two have been mainly based in Aotearoa New Zealand, one in Australia and the fourth in the United Kingdom, but they have maintained social (and some intellectual) contact ever since. Their quite divergent careers and career strategies are sociologically set against some of the social characteristics of their times. The accounts of each are far from definitive, but provide some useful insights into career contingencies which hopefully will provoke contemplation.